Performance analysis of a 10-MW wind farm in a hot and dusty desert environment. Part 1: Wind resource and power generation evaluation. (October 2021) - Al-Rasheedi, Majed; Al-Khayat, Mohammad; Gueymard, Christian A.; Ellen Haupt, Sue; Kosović, Branko; Al-Qattan, Ayman; Lee, Jared A.
Abstract: This study provides performance analysis results obtained from the 10-MW (five 2-MW turbines) Shagaya pilot wind farm located in a desert area of Kuwait, where hot and dusty conditions prevail and constitute engineering challenges. The 2-year operational data analyzed here provide unique results that elucidate the effects of such conditions on turbines' operation. With a long-term average wind speed of 7.9 m/s at 80-m height, the site offers excellent wind power development potential. The performance analysis of the wind farm conducted here includes: power curve, power coefficient, capacity factor, turbulence intensity, and turbine availability. The study also includes a comparison between the actual and potential annual energy production, as well as wind farm energy losses due to the technical availability. The wind farm recorded a remarkably high capacity factor (70%) during the hot summer months, as a result of sustained high wind speeds and high technical availability. For the first year of operation, the wind farm's annual capacity factor and energy production were 45.2% and ≈40 GWh, respectively, decreasing to 42.1% and ≈37 GWh in the second year. This analysis presents new information for the wind energy industry to consider in the development of wind farms in hot desert environments.